Comparison of electrochemical hydrogen storage and Coulombic efficiency of ZnAl2O4 and ZnAl2O4-impregnated TiO2 synthesized using green method. (10th April 2018) - Gholami, Tahereh; Salavati-Niasari, Masoud; Sabet, Mohammad; Abbasi, Ali
Abstract: In this experimental work, we synthesized ZnAl2 O4 and ZnAl2 O4 -TiO2 nanostructures with the help of two green reagents namely olive leaf and green tea extracts. We used different analysis to study the synthesized products. We utilized X-ray diffraction (XRD) patterns to study the crystal phase of the products. The chemical compositions of the products were characterized with energy dispersive X-ray spectroscopy (EDS) and Fourier transform infrared (FT-IR) analysis. In addition, we employed transmission electron microscopy (TEM) and scanning electron microscopy (SEM) images to study the size and morphology of products. The results showed the reagents have a meaningful effect on the product size and morphology because of their capping agent effect during the synthesis of the nanostructures. The porosity of samples was investigated by BET analysis. Based on our knowledge, for the first time, the electrochemical hydrogen storage and Columbic efficiency of ZnAl2 O4 synthesized via essential oil of olive leaf and green tea were investigated via chronopotentiometry method in KOH (6 M) electrolyte. The results showed the synthesized nanocomposites of ZnAl2 O4 with TiO2, improve the capacity of ZnAl2 O4 spinel for the hydrogen storage. Highlights: The ZnAl2 O4 spinel was synthesized via green tea and olive leaf extract. Hydrogen storage capacities of ZnAl2 O4 and ZnAl2 O4 /TiO2 were compared. The Coulombic efficiency of samples was calculated, for the first time. The discharge capacity increased with the increase of cycle number. Hydrogen adsorption sites increased by repeating cycles of charge and discharge.